Aplikasi Augmented Reality Stadion Patriot Candrabhaga Berbasis Android dengan Unity - Nurul Adhayanti (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Candrabhaga Stadium is located in Bekasi City. Although the stadium has many functions, soccer matches are the most common that take place there. One of the oldest stadiums in Indonesia. To host the West Java Regional Sports Week IV in 1984, it was built in 1980, and has a capacity of 5,000 to 10,000 spectators. The author designed an android-based AR application for Patriot Candrabhaga stadium. The application aims to provide information to spectators who will come and who already have plans to visit this stadium. This application was created using Unity to create AR, Blender to create 3D models, and Vuforia while storing target images used in the application. This AR application uses Android v4.4 (Kitkat).